Relationship between chemical composition and in situ rumen degradation characteristics of maize silages in dairy cows. (15th July 2014) - Ali, M.; van Duinkerken, G.; Cone, J. W.; Klop, A.; Blok, M. C.; Spek, J. W.; Bruinenberg, M. H.; Hendriks, W. H.
<x content-type="archive" xml:space="preserve">Abstract</x> Several in situ studies have been conducted on maize silages to determine the effect of individual factors such as maturity stage, chop length and ensiling of maize crop on the rumen degradation but the information on the relationship between chemical composition and in situ rumen degradation characteristics remains scarce. The objectives of this study were to determine and describe relationships between the chemical composition and the rumen degradation characteristics of dry matter (DM), organic matter (OM), CP, starch and aNDFom (NDF assayed with a heat stable amylase and expressed exclusive of residual ash) of maize silages. In all, 75 maize silage samples were selected, with a broad range in chemical composition and quality parameters. The samples were incubated in the rumen for 2, 4, 8, 16, 32, 72 and 336 h, using the nylon bag technique. Large range was found in the rumen degradable fractions of DM, OM, CP, starch and aNDFom because of the broad range in chemical composition and quality parameters. The new database with in situ rumen degradation characteristics of DM, OM, CP, starch and aNDFom of the maize silages was obtained under uniform experimental conditions; same cows, same incubation protocol and same chemical analysis procedures. Regression equations were developed with significant predictors (P<0.05) describing moderate and weak relationships between the chemical composition and the washout fraction, rumen undegradable fraction, potentially rumen degradable fraction, fractional degradation rate and effective rumen degradable fraction of DM, OM, CP, starch and aNDFom.